Subjective Quality Measurement of Speech Its Evaluation, Estimation and Applications - Kondo, Kazuhiro; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
It is becoming crucial to accurately estimate and monitor speech quality in various ambient environments to guarantee high quality speech communication. This practical hands-on book shows speech intelligibility measurement methods so that the readers can start measuring or estimating speech intelligibility of their own system. The book also introduces subjective and objective speech quality measures, and describes in detail speech intelligibility measurement methods. It introduces a diagnostic rhyme test which uses rhyming word-pairs, and includes: An investigation into the effect of word familiarity on speech intelligibility. Speech intelligibility measurement of localized speech in virtual 3-D acoustic space using the rhyme test. Estimation of speech intelligibility using objective measures, including the ITU standard PESQ measures, and automatic speech recognizers.
Speech Quality -- The Diagnostic Rhyme Test -- The Effect of Word Familiarity on the DRT Scores -- Examples of Degraded Speech Intelligibility Measurements Using the Japanese DRT -- DRT Evaluation of Speech Intelligibility in Virtual 3-D Acoustic Speech with Competing Noise -- Estimation of DRT Scores Using Objective Measures -- Summary.
Keywords: Engineering; Translators (Computer programs).; Computational linguistics; Engineering; Signal, Image and Speech Processing; Language Translation and Linguistics; Computational Linguistics